Ordering Christian society through exclusion: the strange history of Cluny. - Iogna-Prat, Dominique (Early Medieval Europe, 2005)
Addresses the issues of the ecclesial reordering and church reform that took place in the eleventh and twelfth centuries, through the strange history of Cluny, a small town in France, and its ninth abbot, Peter the Venerable. Discursive terrain between ecclesiology and political theology; Question of ecclesial inclusiveness; Relationship between order and exclusion.